2021
DOI: 10.1186/s12889-021-11421-4
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of anthropometric indices and its association with NCDs among the older adults of India: evidence from LASI Wave-1

Abstract: Background The purpose of this study is to assess the status of physical body indices such as body mass index (BMI), waist circumference (WC), and waist-to-hip ratio (WHR) among the older adults aged 45 and above in India. Further, to explore the association of anthropometric indices with various non-communicable morbidities. Methods The study uses secondary data of the Longitudinal Ageing Survey’s first wave in India (2017–18). The national repres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 48 publications
1
10
0
Order By: Relevance
“…Other population-based studies conducted in low and middle income countries also found relationships between multi-morbidity and measures of waist circumference and waist-to-hip ratio in older ages [ 22 , 49 ]. The finding is in agreement with a recent study in India that found that adults aged 45 and above with obesity and high-risk waist circumference or waist-hip ratio were more likely to develop cardiovascular diseases than their counterparts [ 50 ], and another study reporting that a higher BMI among general population is associated with a greater prevalence of chronic diseases [ 51 ].…”
Section: Discussionsupporting
confidence: 92%
“…Other population-based studies conducted in low and middle income countries also found relationships between multi-morbidity and measures of waist circumference and waist-to-hip ratio in older ages [ 22 , 49 ]. The finding is in agreement with a recent study in India that found that adults aged 45 and above with obesity and high-risk waist circumference or waist-hip ratio were more likely to develop cardiovascular diseases than their counterparts [ 50 ], and another study reporting that a higher BMI among general population is associated with a greater prevalence of chronic diseases [ 51 ].…”
Section: Discussionsupporting
confidence: 92%
“…Central obesity includes several established and novel indices. Waist circumference (WC) is a commonly used clinical indicator that is strongly associated with the development of CVD, diabetes, hypertension, cancer, and kidney diseases [14,15]. However, WC does not take into account differences in height and therefore may lead to overestimating the risk for taller people or underestimating the risk for shorter people.…”
Section: Introductionmentioning
confidence: 99%
“…On full-text assessment, most exclusions (n=85) were of studies performing only correlation analyses between anthropometric measures and CVD incidence. The number of participants in included studies varied between 140 and 59 037 24 25. There were 25 (83.3%) included studies in India19 24–47 and three (10%) in Bangladesh 48–50.…”
Section: Resultsmentioning
confidence: 99%
“…The number of participants in included studies varied between 140 and 59 037 24 25. There were 25 (83.3%) included studies in India19 24–47 and three (10%) in Bangladesh 48–50. The remaining two studies were conducted in Mauritian51 and Pakistani52 populations, respectively.…”
Section: Resultsmentioning
confidence: 99%